2021
DOI: 10.1186/s43093-021-00106-4
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity risk and stock returns: empirical evidence from industrial products and services sector in Bursa Malaysia

Abstract: This study investigates the impact of liquidity risk on stock returns of 149 firms in the industrial products and services sectors of Bursa Malaysia from January 2000 to December 2018 with a monthly frequency dataset. This study employed the two-stage standard procedures in asset pricing to estimate the significant effect of liquidity risk on industrial products and services stock returns. The results show that the investors require liquidity premium for stocks whose illiquidity co-moves with market illiquidit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Ekinci and Poyraz [ 31 ] based on Turkey showed that there is a negative relationship between CR and FP. Musneh et al [ 74 ] provide indication on the significance of risk in clarifying the cross-sectional stock returns difference in the industrial services and products sector on Bursa Malaysia. Several studies approved this negative association across different contexts (e.g., Abdelaziz et al [ 1 ] for MENA region, Bishnu [ 18 ] for Nepal, Kingu et al [ 60 ] for Tanzania, Isanzu [ 46 ] for China).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Ekinci and Poyraz [ 31 ] based on Turkey showed that there is a negative relationship between CR and FP. Musneh et al [ 74 ] provide indication on the significance of risk in clarifying the cross-sectional stock returns difference in the industrial services and products sector on Bursa Malaysia. Several studies approved this negative association across different contexts (e.g., Abdelaziz et al [ 1 ] for MENA region, Bishnu [ 18 ] for Nepal, Kingu et al [ 60 ] for Tanzania, Isanzu [ 46 ] for China).…”
Section: Literature Review and Hypothesis Developmentmentioning
confidence: 99%
“…Therefore, we used the weighted average cost of equity based on the CAPM framework due to its strong theoretical underpinnings. The CAPM explains how the firm risk is related to its expected returns [ 71 ]. Thus, the weighted average cost of equity is calculated by multiplying the equity risk premium of the market with the beta of the firm’s stock plus an inflation-adjusted risk-free rate.…”
Section: Methodsmentioning
confidence: 99%
“…However, lending growth relies on financial liberalization and banking reforms, which at some point is negatively affected by the selection of subprime customers that gives rise to weaker asset quality (Aysan & Ozturk, 2018 ). Similarly, the higher non-performing assets (herein after NPA) negatively affect bank’s profitability (Epure & Lafuente, 2015 ; Das & Uppal, 2021 ; Hunjra et al, 2020 ; Musneh et al, 2021 ; Ahmed et al, 2022 ), which enhances the financing cost, and reduces the supply of future credits (Aiyar et al, 2015 ). The private sector predicts the future credit default of banking companies and uses it as a driving force to make decisions and gain confidence in expanding or contracting their credit exposure in future (Bordalo et al, 2018 ).…”
Section: Literature Reviewmentioning
confidence: 99%